Geometry Optimalization of the Ventilated Insulating Panel - Wójcik, Andrzej; Wójcik, Jakub; Gryfin, Witold; Konca, Piotr; Gawin, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
An EPS ventilated panel, which may be applied as an external insulation to humid walls, is investigated. Dimensions of the air channel sections have been determined using the ANSYS software. Afterwards, the drying rate of the walls externally insulated with EPS, mineral wool and EPS ventilated panel has been compared using the WUFI software. The ventilated panel increases the drying rate when compared with the standard polystyrene panel and increases the heat loss through the wall by less than 20%.
Keywords: EPS; insulation humid walls; ventilated; ventilated channels; drying rate of wall; płyta styropianowa; izolacja wilgotnych ścian; wentylacja; kanały wentylacyjne; szybkość schnięcia